(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
This article presents a clinical observation of the complex course of botulism in school-aged children. Laboratory testing tactics, treatment approach, and clinical effectiveness of treatment are also shown